The Role of B Cells and Antibodies in Multiple Sclerosis, Neuromyelitis Optica, and Related Disorders - Häusser-Kinzel, Silke; Weber, Martin S. (Frontiers in Immunology, 2019)
Our pathophysiological concept of the most common central nervous system demyelinating disease, multiple sclerosis, strikingly evolved by recent discoveries suggesting that B lymphocytes substantially contribute in its initiation and chronic propagation. In this regard, activated B cells are nowadays considered to act as important antigen-presenting cells for the activation of T cells and as essential source of pro-inflammatory cytokines. Hereby, they create a milieu in which other immune cells differentiate and join an orchestrated inflammatory infiltration of the CNS. Without a doubt, this scientific leap was critically pioneered by the empirical use of anti-CD20 antibodies in recent clinical MS trials, which revealed that the therapeutic removal of immature and mature B cells basically halted development of new inflammatory flares in otherwise relapsing MS patients. This stabilization occurred largely independent of any indirect effect on plasma cell-produced antibody levels. On the contrary, peripherally produced autoantibodies are probably the most important B cell component in two other CNS demyelinating diseases which are currently in the process of being delineated as separate disease entities. The first one is neuromyelitis optica in which an antibody response against aquaporin-4 targets and destroys astrocytes, the second, likely distinct entity embraces a group of patients containing antibodies against myelin oligodendrocyte glycoprotein. In this review, we will describe and summarize pro-inflammatory B cell properties in these three CNS demyelinating disorders; we will however also provide an overview on the emerging concept that B cells or B cell subsets may exert immunologically counterbalancing properties, which may be therapeutically desirable to maintain and foster in inflammatory CNS demyelination. In an outlook, we will discuss accordingly, how this potentially important aspect can be harnessed to advance future B cell-directed therapeutic approaches in multiple sclerosis and related diseases.